Effect of CYP2C9 rs2860905 Polymorphism on the Efficacy of Losartan in Pakistani Hypertensive Patients - Haider, Qurat Ul Ain; Saeed , Hafsa; Ikram, Wajiha; Ikram, Usama; Hussain, Misbah (Current Trends in OMICS, 2023)
Hypertension is a multifactorial disease characterized by high blood pressure in blood vessels. It is caused by the dysregulation of renin angiotensin aldosterone system (RAAS). It is a major risk factor for other metabolic diseases including cardiovascular diseases, diabetes, and others. Various RAAS targeting drugs such as losartan are prescribed as the first line therapy to treat hypertension. However, their efficacy varies among individuals owing to genetic variations in drug binding substrates or drug metabolizing enzymes, which convert the prodrug to active drug. CYP2C9 gene encodes for an enzyme which metabolizes losartan. Various studies have concluded that genetic variations in CYP2C9 affect the response of losartan due to the variation in its metabolism. Thus, the current study aimed to check the effect of CYP2C9 rs2860905 G>A polymorphism on the efficacy of losartan. For this purpose, a total of 48 subjects were selected and genotyped for rs2860905 polymorphism using in-house developed tetra-ARMS-PCR. The subjects were divided into responding (n=34) and non-responding (n=14) groups on the basis of their blood pressure after treatment with losartan. Statistical analysis demonstrated that rs2860905 GG genotype was more prevalent in the responding group as compared to the non-responding group (50% vs. 36%). Multinomial regression analysis showed that the carriers of GA or AA genotype did not respond to losartan treatment efficiently as compared to those of GG genotype. However, these results could not achieve statistical significance. To conclude, CYP2C9 rs2860905 G>A polymorphism does not affect the efficacy of losartan in Pakistani hypertensive subjects.